Meaningful Reform in the Western Balkans : Between Formal Institutions and Informal Practices. - Gordy, Eric.; Efendic, Adnan (Bern : Peter Lang AG International Academic Publishers, 2019)
This book contains collection of articles which provide policy implications related to the problem of achieving substantive reform on the basis of harmonising legislation in Western Balkan (WB) countries with the standards of the European Union (EU).
Cover -- Contents -- 1. Engaging Policy to Address Gaps Between Formality and Informality in the Western Balkans (Eric Gordy / Adnan Efendic) -- 2. Europeanisation and Institutionalisation of EU Rules in the Western Balkans (Ivan Damjanovski / Marko Kmezic) -- 3. Implementation and Enforcement of EU Rules in South East Europe (Miran Lavrič / Reana Senjković / Rudi Klanjšek) -- 4. The Cost of Informal Networking in the Western Balkans Region Matters! (Adnan Efendic / Alena Ledeneva) -- 5. How to Sustainably Decrease Clientelism and Ensure Fair Political Competition in the WB? The Case for Introducing Standing Parliamentary Committees (Misha Popovikj / Borjan Gjuzelov / Jovan Bliznakovski) -- 6. Leaders' Meetings: Facilitating or Replacing the Formal Political Processes in the Western Balkan Countries? (Vjollca Krasniqi / Nenad Markovikj / Ilina Mangova / Enriketa Papa-Pandelejmoni / Jovan Bliznakovski) -- 7. Informality and Everyday Life: How 'Things Get Done' in Contemporary Western Balkan Societies (Vjollca Krasniqi / Enriketa Papa-Pandelejmoni / Armanda Hysa / Gentiana Kera) -- 8. Formal and Informal Institutions in Policy - Evidence from South East Europe (Mirza Mujarić / Ismet Kumalić) -- Appendix -- Notes on Contributors.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books